Acute interstitial pneumonia triggered by strenuous exercise - Markoska, Frosina (Respir Med Case Rep, 2020)
Acute interstitial pneumonia (AIP) is a rare and severe form of idiopathic interstitial lung disease. Treatment is primarily supportive with supplemental oxygenation and mechanical ventilation. Prognosis is poor, but long-term survival is possible after recovery from AIP. We present a case of a 48-years-old previously healthy female who was admitted due to acute shortness of breath and respiratory failure which started three days after she ran a half-marathon. After excluding infectious causes and connective-tissue diseases, a presumptive diagnosis of AIP was made based on clinical and radiological characteristics. The patient was successfully treated with high-dose corticosteroids and mycophenolate mofetil.